The runaways : a study of enslaved, apprenticed and indentured labour flight at the Cape in the emancipation era, 1830-42 - Bergemann, Karl Jason (Stellenbosch : Stellenbosch University, 2024)
Thesis (DPhil)--Stellenbosch University, 2024.